Collaborative Governance’s Risk Management (Case Study: Implementation of Tobacco Control Policy in Kulonprogo and Pekalongan City) - Murti, Awang Daru; Baiquni, Muhammad; Lele, Gabriel (Journal of Governance and Public Policy, 2023)
This article explored collaborative governance risk management on implementing tobacco control policy in Kulonprogo Regency and Pekalongan City. The research methods used qualitative methods based on primary and secondary data. The authors collected the primary data through interviews with some actors. In contrast, the secondary data comprised online mass media and previous research on relevant topics. This article also uses the tool Nvivo12 Plus to help with data processing. The results showed that the collaborative governance of Kulonprogo Regency and Pekalongan City had some risks in their collaboration. Kulonprogo Regency could resolve those risks through decision-making to achieve the integrated mechanism. This step is easy to implicate because the actor has high cooperation to solve their problem through a joint decision. While the risk collaboration of Pekalongan city could not be solved properly cause of the lack the mechanical integration of the actor in that collaboration. The actor has different principles and impacts on a joint decision to achieve an integrated mechanism when solving the problems.